Metalloprotease meprin beta in rat kidney: glomerular localization and differential expression in glomerulonephritis. - Beatrice Oneda; Nadège Lods; Daniel Lottaz; Christoph Becker-Pauly; Walter Stöcker; Jeffrey Pippin; Maya Huguenin; Daniel Ambort; Hans-Peter Marti; Erwin E Sterchi (PLoS ONE, 2008)
Meprin (EC 3.4.24.18) is an oligomeric metalloendopeptidase found in microvillar membranes of kidney proximal tubular epithelial cells. Here, we present the first report on the expression of meprin beta in rat glomerular epithelial cells and suggest a potential involvement in experimental glomerular disease. We detected meprin beta in glomeruli of immunostained rat kidney sections on the protein level and by quantitative RT-PCR of laser-capture microdissected glomeruli on the mRNA level. Using immuno-gold staining we identified the membrane of podocyte foot processes as the main site of meprin beta expression. The glomerular meprin beta expression pattern was altered in anti-Thy 1.1 and passive Heymann nephritis (PHN). In addition, the meprin beta staining pattern in the latter was reminiscent of immunostaining with the sheep anti-Fx1A antiserum, commonly used in PHN induction. Using Western blot and immunoprecipitation assays we demonstrated that meprin beta is recognized by Fx1A antiserum and may therefore represent an auto-antigen in PHN. In anti-Thy 1.1 glomerulonephritis we observed a striking redistribution of meprin beta in tubular epithelial cells from the apical to the basolateral side and the cytosol. This might point to an involvement of meprin beta in this form of glomerulonephritis.